TRATAMENTO DE EFLUENTE PROVENIENTE DA LAVAGEM DE RESÍDUOS DE CONSTRUÇÃO E DEMOLIÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2016)
This paper aims to propose a treatment system for wastewater from the construction and demolition waste washing water (RCD). Therefore, the physico-chemical characterization of a lot of stuff, from washing effluent in different proportions of water was performed. A mass of material was washed following the criteria established in the Brazilian Norm Standard MERCOSUR 46 of 2003, for determination by physical removal of the pulverulent material (particles smaller than 75 μm), which damage the quality of the mortar. The RCD has been classified as fine aggregate with a maximum size of 4,8 mm and feature average fineness modulus of 2,77. For washing RCD according to the specified in the standard no specific amount of water for performing the process. Thus, the present study aimed to optimize this amount obtaining an optimum rate of mass RCD for a water volume of 1,67 : 1,00. The resulting effluent from the washing of ash RCD presented pH between 7,54 and 8,34, acidity from 9,09 to 15,25 mg CO2.L-1 and 10,33 to 17,33 mg of CaCO3.L-1 . The turbidity of 70,93 NTU varied more than 300 NTU. Following proposed treatment for the effluent with three treatment options: a sedimentation tank; by combined sedimentation tank in series with sand filter; processes for coagulation, flocculation and sedimentation. And after the analysis of these three systems, it was observed that all showed efficiency in some parameters analyzed, highlighting that the turbidity was removed by 99 % in the three cases. The process was less efficient coagulation, flocculation and settling by the use of the coagulant of aluminum sulfate in 100 mg.L-1 concentration. It also emphasizes that the COD was removed more than 90 % in the three proposed processes. Thus, it was concluded that the best treatment system was observed by physical and biological combined removal by settling tank in series with a sand filter.
Keywords: resíduo de construção e demolição; material pulverulento; caracterização; argamassa; construction and demolition waste; powdery material; characterization; mortar; CNPQ::ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL